Chemoselective Preparation of 1,1-Diacetates from Aldehydes, Mediated by a Keggin Heteropolyacid Under Solvent Free Conditions at Room Temperature - G. Romanelli; P. Dimitroff; P. Vázquez; J. C. Autino (E-Journal of Chemistry)
A simple, general and efficient method has been developed for the conversion of aldehydes to 1,1-diacetates using acetic anhydride, a catalytic amount of non commercial Keggin heteropolyacid (H6 PalMo11O40) (1% mol) in solvent free conditions at room temperature. Aromatic and aliphatic, simple and conjugated aldehydes were protected with excellent yields.